A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution - Torres-Pachón, Mónica; Novelo-Gutiérrez, Rodolfo; Ruiz-Sanchez, Eduardo (Zootaxa, 2019)
A synopsis of the 13 species of Phyllogomphoides Belle, 1970 known to occur within Mexico is presented. Taxonomic keys for males are based primarily on morphology of anterior and posterior hamules, caudal appendages and of the vulvar lamina in females and includes full descriptions for each species accompanied by high-resolution photographs, drawings, comparative diagnostic notes, natural history and distribution maps. Females of P. danieli González & Novelo, 1990 and P. nayaritensis Belle, 1987 are described for the first time. Moreover, new records for P. albrighti (Needham, 1950) for the states of Guerrero; P. danieli González & Novelo, 1990 for Colima, Guerrero and San Luis Potosí; P. duodentatus Donnelly, 1979 for Oaxaca; P. luisi González & Novelo, 1990 for Nayarit, and P. pugnifer Donnelly, 1979 for San Luis Potosí, are also provided.